Syrian Hamster as an Animal Model for the Study of Human Influenza Virus Infection - Iwatsuki-Horimoto, Kiyoko; Nakajima, Noriko; Ichiko, Yurie; Sakai-Tagawa, Yuko; Noda, Takeshi; Hasegawa, Hideki; Kawaoka, Yoshihiro (Journal of virology, 2018)
Ferrets and mice are frequently used as animal models for influenza research. However, ferrets are demanding in terms of housing space and handling, whereas mice are not naturally susceptible to infection with human influenza A or B viruses. Therefore, prior adaptation of human viruses is required for their use in mice. In addition, there are no mouse-adapted variants of the recent H3N2 viruses, because these viruses do not replicate well in mice. In this study, we investigated the susceptibility of Syrian hamsters to influenza viruses with a view to using the hamster model as an alternative to the mouse model. We found that hamsters are sensitive to influenza viruses, including the recent H3N2 viruses, without adaptation. Although the hamsters did not show weight loss or clinical signs of H3N2 virus infection, we observed pathogenic effects in the respiratory tracts of the infected animals. All of the H3N2 viruses tested replicated in the respiratory organs of the hamsters, and some of them were detected in the nasal washes of infected animals. Moreover, a 2009 pandemic (pdm09) virus and a seasonal H1N1 virus, as well as one of the two H3N2 viruses, but not a type B virus, were transmissible by the airborne route in these hamsters. Hamsters thus have the potential to be a small-animal model for the study of influenza virus infection, including studies of the pathogenicity of H3N2 viruses and other strains, as well as for use in H1N1 virus transmission studies. IMPORTANCE We found that Syrian hamsters are susceptible to human influenza viruses, including the recent H3N2 viruses, without adaptation. We also found that a pdm09 virus and a seasonal H1N1 virus, as well as one of the H3N2 viruses, but not a type B virus tested, are transmitted by the airborne route in these hamsters. Syrian hamsters thus have the potential to be used as a small-animal model for the study of human influenza viruses.